Role of microRNAs on T cell differentiation during immune responses in vivo - Cunha, Carolina (2021)
CD4+ T cells are key players in host defense against pathogens, but an incorrect balance between CD4+ T cell subsets, namely pro-inflammatory effector cells, including T helper 1 (Th)1 and Th17 cells (IFN-γ- and IL-17-producers, respectively), and anti-inflammatory regulatory cells (Treg; Foxp3+ subset), can lead to immune-mediated diseases. MicroRNAs (miRNAs) are small non-coding RNAs that negatively regulate gene expression at the post-transcriptional level. While individual miRNAs were shown to regulate the differentiation of specific CD4+ T cell populations, a holistic approach based on in vivo responses is missing and is critical to understanding how miRNA networks control this balance under physiological conditions. To address this, we have established a triple reporter mouse for Ifng, Il17, and Foxp3, and subject it to experimental autoimmune encephalomyelitis (EAE). We perform miRNA-seq analysis on Th1, Th17, and Treg cells isolated from the spleen (SPL) and lymph nodes (LNs) at the peak-plateau stage and found that 110 miRNAs are differentially expressed between effector and regulatory subsets. We further selected 8 candidate miRNAs that were specifically upregulated in one population versus the others. Both overexpression and inhibition studies showed that miR-126a limits IL-17+ expression in Th17 cells in vitro. Treatment with antagomiRs in vivo showed that silencing miR-122 increased the number of IL-17+ cells in the LNs and precipitated the onset of EAE, whereas inhibition of miR-1247 decreased the severity of the disease by reducing the number of IFN-γ+ cells, also in the LNs. Additionally, we identified IL-6 and TGF-β as the key cytokines upstream of miR-126a and miR-1247 expression, respectively. While both IL-6 and TGF-β also induce miR-122 expression, we found that IL-23 and IL-1β repress its expression. Interestingly, and given that IL-23 and IL-1β are critical to inducing Th17-mediated pathogenicity, we have consistently observed a pathogenic gene signature in CNS-derived Th17 cells when compared to peripheral Th17 cells with concomitantly decreased levels of miR-126a and miR-122. Overall, our results suggest that miR-126a and miR-122 regulate IL-17 expression and the pathogenic phenotype of Th17 cells to prevent excessive inflammation in the periphery while miR-1247 maintains the inflammatory phenotype of Th1 cells in an anti-inflammatory environment.